Rotigotine Objectively Improves Sleep in Parkinson’s Disease: An Open-Label Pilot Study with Actigraphic Recording - Giovanna Calandra-Buonaura; Pietro Guaraldi; Andrea Doria; Stefano Zanigni; Stefania Nassetti; Valentina Favoni; Sabina Cevoli; Federica Provini; Pietro Cortelli (Parkinson's Disease)
Sleep disturbances represent important predictors of poor quality of life (QoL) in Parkinson’s disease (PD). This open-label pilot study aimed to objectively assess, by means of actigraphic recording, effect of rotigotine on sleep in PD patients with self-reported sleep complaints. 15 PD patients underwent one-week actigraphic recording before (T0) and during (T1) rotigotine treatment, which was titrated to the dose subjectively improving motor symptoms (4–8 mg/24 h). Sleep disturbances, daytime sleepiness, cognitive performance, QoL, and depression were also evaluated with questionnaires. Actigraphic recordings showed a significant reduction in nocturnal motor activity and mean duration of wake episodes after sleep onset during rotigotine treatment compared to baseline. In 10 patients presenting objective evidence of poor sleep quality at T0 (sleep efficiency ≤ 85%), rotigotine also significantly improved other sleep parameters and further reduced nocturnal motor activity and mean duration of wake episodes. A significant decrease in number and duration of daytime sleep episodes was also observed at T1. Finally we confirmed that rotigotine significantly improves perceived sleep quality and QoL. Our study showed for the first time that rotigotine is associated with an objective improvement of nocturnal and diurnal sleep disturbances in PD patients with self-reported sleep complaints. This study is registered with AIFA-observational study registry number 12021.